If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14xcubed + -68xsquared + -10x = 0 Reorder the terms: -68adeqrsux + 14bcdeux + -10x = 0 Solving -68adeqrsux + 14bcdeux + -10x = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-14bcdeux' to each side of the equation. -68adeqrsux + 14bcdeux + -14bcdeux + -10x = 0 + -14bcdeux Combine like terms: 14bcdeux + -14bcdeux = 0 -68adeqrsux + 0 + -10x = 0 + -14bcdeux -68adeqrsux + -10x = 0 + -14bcdeux Remove the zero: -68adeqrsux + -10x = -14bcdeux Add '10x' to each side of the equation. -68adeqrsux + -10x + 10x = -14bcdeux + 10x Combine like terms: -10x + 10x = 0 -68adeqrsux + 0 = -14bcdeux + 10x -68adeqrsux = -14bcdeux + 10x Divide each side by '-68deqrsux'. a = 0.2058823529bcq-1r-1s-1 + -0.1470588235d-1e-1q-1r-1s-1u-1 Simplifying a = 0.2058823529bcq-1r-1s-1 + -0.1470588235d-1e-1q-1r-1s-1u-1
| F=9/5k-459.67 | | 6.2+5-1.4=4.8+5 | | 3x+2y+z=50 | | 2/7s=6 | | 2p/3+26=22 | | 10=x/8 | | 4x-1=7x-13 | | 8z-16=4z | | 3x+16=10x+(-12) | | 16z-36=4z | | 6(7x+2)=-324 | | 2(3x-1)=4x+1 | | 16x+12y=20 | | 2x-13=2x-2 | | 6d+3d-3d+6=5d | | 34=1.7x | | 5(2x+3)=7(x+1) | | 7a=0.21 | | 3x+16=10x-12 | | 7x-4=3x+6 | | -5(4+6x)=340 | | 9(1.8x+2)=13.8+30 | | 7x+3=80-x | | -5x+8=-76+2x | | d^2-14d=41 | | 59-11x=13+12x | | 12+3.00=16x | | t^2+2t-30=0 | | j^2-2j=19 | | 7x+5=-16+4x | | 5.9=-6+x | | D=-25-4ac |